About the principles of "universalism" and "cosmism" in modern architecture as an expression of the common human ideas of the contemporary time - Portnova,; Portnova, T. (International Journal of Psychosocial Rehabilitation, 2020)
This article dwells on the subject of universalism in modern European architecture of the XXth - early XXIst century, that's becoming a multi-functional and aspiring to the expression of large "macro-cosmic" volumes and spaces. This conception is justified by its power which breaks familiar stereotypes in the field of the architectural art. Unlike a monumental architecture of ancient civilizations, that was a kind of expression of a sacral function, the modern one represents the "philosophy" of the world view and society, that's based on principles of environmental understanding and perception. It's noted that macroscopic architectural objects of modernity are the sphere of human activity of our time, which becomes more and more ecologically colored, reflecting actual human needs in a comfortable, healthy environment. The perspective of this phenomenon is traced.